A qualitative study of abortion care providers' perspectives on telemedicine medical abortion provision in the context of COVID-19. Issue 3 (30th November 2021) - Reynolds-Wright, John Joseph; Boydell, Nicola; Cameron, Sharon; Harden, Jeni
Abstract : Background: Telemedicine for medical abortion care was rapidly introduced in Great Britain in response to the COVID-19 pandemic. A growing body of literature demonstrates that telemedicine abortion care is safe, effective and highly acceptable to patients. Less is known about the perspectives of abortion care providers (ACPs). Methods: Qualitative research within the telemedicine abortion service in Lothian (Edinburgh and surrounding region), UK. We conducted qualitative in-depth interviews with ACPs between May and July 2020 (doctors, n=6; nurses, n=10) and analysed the data thematically. Results: We present three themes from our qualitative analysis: (1) Selective use of ultrasound – the move away from routine ultrasound for determination of gestational age was generally viewed positively. Initial anxiety about non-detection of ectopic pregnancy and later gestations was expressed by some ACPs, but concerns were addressed through clinical practice and support structures within the clinic. (2) Identifying safeguarding issues – in the absence of visual cues some ACPs reported concerns about their ability to identify safeguarding issues, specifically domestic violence. Conversely it was acknowledged that teleconsultations may improve detection of this in some situations. (3) Provision of information during the consultation – telephone consultations were considered more focused than in-person consultations and formed only part of the overall 'package' of information provided to patients, supplemented by online and written information. Conclusions: ACPs providing telemedicine abortion care value this option for patients and believe it should remain beyond the COVID-19 pandemic. Safeguarding patients and the selective use of ultrasound can be initially challenging; however, with experience, staff confidence improves.